PENGAWASAN PEMBEBASAN BERSYARAT TERHADAP TAHANAN KOTA PADA MASA PANDEMI COVID-19 - Nur Hidayah; Zul akli; Malahayati M (Fakultas Hukum Universitas Malikussaleh, 2022)
Abstract Supervision according to Victor M. Situmorang and Jusuf Juhir is every effort and action in order to know the extent to which the implementation of tasks carried out according to the provisions and objectives to be achieved. The duties and functions of Community Guidance are regulated in several regulations including, namely the Decree of the Minister of Justice of the Republic of Indonesia Number M.01-PK.04.10 of 1998 concerning Duties, Obligations, and Conditions for Community Guidance, RI Law Number 11 of 2012 concerning the Judicial System Child Crime, regarding the duties and functions of Community Guidance and adaptations carried out by Community Advisors during the Covid-19 pandemic. The research objectives in this study were to find out and explain how to monitor conditional release of city prisoners during the Covid-19 pandemic, and to find out and explain how the consequences of the parole policy on city prisoners in the community during the Covid-19 pandemic and efforts the government did in handling the conditional release of city detention during the Covid-19 pandemic. The research method used in this research is: This type of juridical normative research. With a statutory approach, and a conceptual approach. The nature of the research in this thesis is descriptive research. And the form of this research research is a descriptive form. Based on the results of the study, it can be seen that in supervising convicts who get parole, the government carries out various programs to deal with convicts who get parole during the COVID-19 pandemic, namely by collaborating between community counselors and the community and involving the families concerned to anticipate when things go wrong. Keywords : Surveillance, parole, Covid-19 pandemic